Factors influencing tertiary students' choice of study mode - Bailey, M.; Ifenthaler, Dirk; Gosper, M.; Kretzschmar, M. (2014)
Managing and understanding student's motivations and experiences of learning will be increasingly important as demand for higher education continues to grow and online delivery continues to evolve and expand into open access, on-campus and distance modes of study. It is in the interests of institutions offering two or more modes of study to understand the reasons why students make different choices. This research investigates the importance of six factors (personal, logistics, teaching and learning, learning support, environment, and advice and marketing) influencing 744 students choice of three different modes of study. Findings indicate that there are significant differences in the importance of factors amongst students enrolled in different study modes, although when averaged across all cohorts 'teaching and learning' and 'logistics' factors were the most influential. It is suggested that providing a high level of transparency in the information provided to students is vital for higher education institutions.